An approach to the understanding of equity in health - Sergio Antonio Clavijo Clavijo; Gregory David Villamil Rodríguez; Laura Carolina Olarte Herrera; Ingrid Catherine Castillo Navarrete; Ivette Rocío Rincón Sánchez (Universidad Nacional de Colombia, 2013)
The world health should be considered a social welfare of human beings, since this is a prerequisite for the development of humanity. In the context of human rights, health equity is an inherent principle based on social justice, looking for all individuals regardless of their social, entitled to the same opportunities. Historically, have developed health services that provide social welfare to individuals, but the concept has prevailed mercantilist, which has reduced health systems to simple utilities, ignoring the underlying problems of the population. It is proposed Primary Health Care as an alternative, speaking as population includes the responsibility to ensure health services accessibility and a possible response to the inequalities inherent in a system focused on health insurance. For this study was conducted reflects on the concept of equity, carrying out searches with the terms equity, health, equity in health, health economics, quality health, public health, public health policy, health history, primary health care with the aim of being able to collect partial abstracts or full text. Additional to search for electronic journals, books that will argue the importance of equity in the companies were consulted, different economic models, the history of health and disease; nature relating bills that argument on these definitions were consulted.